PENINGKATAN OUTPUT PRODUKSI DI PT. XYZ - Sudjono, Reza; Rahardjo, Jani (Jurnal Titra, 2014)
PT. XYZ is one of company manufacturing for product pipe gas with many size.Company has a problem in fulfill a demand of customer. Research at PT. XYZ have apurpose to increase the output production. Increasing output product with aimprovement at method and man. Those problems are long duration to exchange theroll, the emptiness of material and appear new production plan suddenly. The givenimprovement to company are make a work instruction for each machine and addedoperator. Estimation of the result improvement is reducing working time about 55-65%,the reduction of time make a good impact within increased the output of production.